Dampak dan Peran Ekonomi Kreatif Jember Fashion Carnaval (JFC) Dalam Pembangunan Sosial Pada Masyarakat Kabupaten Jember - Diva Ummul Nabilla; Rosita Setyaningrum; Isti Kharimah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Social development is important for a region, because it determines the level of welfare of its people.This research will explain how the impact and role of the creative economy of the Jember Fashion Carnival (JFC) is able to help the people of Jember to improve their welfare in terms of the economy. This research will use qualitative research methods with literature study data collection techniques. Research will collect library data, read, take notes, and manage research materials so as to produce accurate data.